Non-consumptive effects of native, alien and invasive alien crayfish on damselfly egg life history and carry-over effects on larval physiology - Szymon Sniegula; Dorota Konczarek; Maciej Bonk; Andrzej Antoł; Nermeen R. Amer; Robby Stoks (NeoBiota)
Invasive alien (IA) predators pose significant threats to native ecosystems, often leading to profound impacts on prey species through both direct and non-consumptive effects (NCE). This study focused on the NCE of predator-induced stress from one native crayfish species, noble (Astacus astacus), compared to one alien danube crayfish (Pontastacus leptodactylus) and two IA crayfish species, signal (Pacifastacus leniusculus) and spinycheek crayfish (Faxonius limosus), on the native damselfly Ischnura elegans. We investigated the direct crayfish cue effect on egg traits as well as potential carry-over effects from the egg stage to the larval stage. We hypothesised that native crayfish cues would lead to more pronounced negative effects on prey traits compared to alien and IA crayfish, due to an evolutionary history of interaction and recognition of these threats. Unexpectedly, compared to native crayfish cues, alien and IA crayfish cues caused significantly higher egg mortality and prolonged developmental times, particularly cues from danube and signal crayfish, while cues from spinycheek crayfish had weaker, yet, still significant effects. Hatching synchrony was reduced and this to the same extent by the cues of all four crayfish species. Notably, cues from both alien and IA crayfish species caused significant carry-over effects, resulting in reduced larval survival, mass and fat content, which were more pronounced for danube and signal crayfish. Native crayfish cues did not induce carry-over effects, suggesting that I. elegans may have evolved a degree of resilience against this predator or that native crayfish produce chemical cues that do not cause a strong antipredator response. Our findings underscore the importance of considering immediate and carry over effects of crayfish on prey traits across multiple life stages, particularly in the context of biological invasions.